Mango Fruit Fly, Marula Fruit Fly, Ceratitis cosyra (Walker) (Insecta: Diptera: Tephritidae) - Gary J. Steck (EDIS)
Ceratitis cosyra is commonly known as the mango fruit fly or marula fruit fly based on its common occurrence in these host plants. Marula is a native African fruit related to mango and sometimes known locally as wild plum. The fly is a serious pest in smallholder and commercial mango across sub-Saharan Africa and has been recorded in Ivory Coast, Kenya, South Africa, Tanzania, Uganda, Zambia and Zimbabwe, where it is more destructive than either Mediterranean fruit fly (Medfly; Ceratitis capitata (Wiedemann)) or the Natal fruit fly (Ceratitis rosa Karsch) (Malio 1979; Labuschagne et al. 1996; Javaid 1979; De Lima 1979; Rendell et al. 1995; Lux et al. 1998). This document is EENY-286, originally published as DPI Entomology Circular 394, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2003.